2009
DOI: 10.1007/s10103-009-0710-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of short- and long-pulse durations when using a 585-nm pulsed dye laser in the treatment of new surgical scars

Abstract: More than 70 million surgical procedures are performed annually in the USA with the majority involving a skin lesion and almost all individuals in their lifetime will have one or more surgical procedures resulting in scars. Patients and physicians alike are thereby motivated to improve the cosmetic outcome of scars. Prior studies have shown that the pulsed dye laser (PDL) is effective in improving the quality and appearance of the scar when using the 585-nm PDL immediately after the removal of sutures. Most pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 11 publications
0
56
0
Order By: Relevance
“…1 Although PDL has been proven safe and effective for the treatment of surgical scars, many recent articles reported that 3 to 4 treatment sessions were necessary to achieve satisfactory results. [2][3][4][5] Many groups began PDL treatment immediately after suture removal, and subsequent treatment was separated by 4 to 10 weeks. [2][3][4] Present published studies found evidence that the PDL using a nonpurpuric pulse duration is more helpful for improving the vascularity and pliability of fresh surgical scars than purpuric settings at the same fluence.…”
mentioning
confidence: 99%
“…1 Although PDL has been proven safe and effective for the treatment of surgical scars, many recent articles reported that 3 to 4 treatment sessions were necessary to achieve satisfactory results. [2][3][4][5] Many groups began PDL treatment immediately after suture removal, and subsequent treatment was separated by 4 to 10 weeks. [2][3][4] Present published studies found evidence that the PDL using a nonpurpuric pulse duration is more helpful for improving the vascularity and pliability of fresh surgical scars than purpuric settings at the same fluence.…”
mentioning
confidence: 99%
“…Their use improved the appearance of hypertrophic scars [8,9]. Nouri et al reported that, the flash lamp-PDL was found to be the best treatment to achieve long-term improvement in the appearance of hypertrophic scars [10].…”
Section: Introductionmentioning
confidence: 99%
“…101 For example, the 585 nm pulsed dye laser improved scar appearance in a study where only part of the scar was treated with laser and the other part remained untreated and served as a control. 130 Proposed mechanisms of action of the 585 nm laser include reduction of TGF-b expression, 131 thermolysis of small vessels, 132 and rearrangement of collagen fibers. 133 1,064 nm Nd-YAG and 1,550 nm Fraxel lasers have also shown some efficacy in improving scar appearance.…”
Section: Stem Cells In 2009 Biernaskie Et Al Deter-mentioning
confidence: 99%